Assessment of the Problems of Attracting Investments to Armenia from the Point of View of the Security Environment - Kyuregyan, Arpine (Journal of Posthumanism, 2025)
Investments play an important role in developing the economy of any country, solving social problems, strengthening the country’s defense and ensuring national security. The purpose of this study is to assess the current problems of Armenia’s investments in a safe environment and, based on them, propose approaches to attracting investments. In order to assess the factors influencing the investment environment, the article used methods of empirical analysis and SWOT. The results of the model and qualitative assessment, developed using mathematical and econometric tools, show that the volume of foreign investment in Armenia is predominantly influenced by the risk of renewed hostilities, intraregional military and political instability, small reserves of natural resources, infrastructural problems, tax rates, tax legislation, and protection of foreign investors. The results of the SWOT analysis show that the Armenian economy is characterized by high foreign policy risks (the risk of an armed conflict with Azerbaijan), as well as the transport blockade, the shortage of natural resources, and the presence of social contradictions, which means that making a forecast for the investment environment in Armenia in accordance with economic conditions will not be qualified by optimistic or positive results and expectations. Consequently, the article suggested implementing targeted measures that would increase new investment flows.